2009
DOI: 10.1007/s12200-009-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of Al x Ga1 − x N/Al y Ga1 − y N multiple quantum wells for deep ultraviolet emission

Abstract: The Al x Ga 1 -x N/Al y Ga 1 -y N multiple quantum well (MQW) structure for deep ultraviolet emission has been grown on sapphire by metal organic chemical vapor deposition (MOCVD). High resolution X-ray diffraction (HRXRD), atomic force microscopy (AFM), and cathodoluminescence (CL) are used to characterize the structural and optical properties of MQWs, respectively. Clear step flows can be observed in the AFM image indicating a two-dimensional growth model. There are many cracks on the surface of the MQW stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 20 publications
7
107
1
1
Order By: Relevance
“…In p+p collisions, the azimuthal distribution of back-to-back dijet pairs is peaked at ∆φ ∼ π, with initial-state and finalstate radiative processes generating acoplanarity that broadens the ∆φ distribution. In nuclear collisions, additional acoplanarity may be induced by jet interactions in hot QCD matter [25,[27][28][29]67], with magnitude related to the jet transport parameterq [27,29,67]. Acoplanarity from vacuum radiation grows with both jet energy and √ s, so that low energy jets may have greatest sensitivity toq [27,29].…”
Section: Medium-induced Acoplanaritymentioning
confidence: 99%
See 2 more Smart Citations
“…In p+p collisions, the azimuthal distribution of back-to-back dijet pairs is peaked at ∆φ ∼ π, with initial-state and finalstate radiative processes generating acoplanarity that broadens the ∆φ distribution. In nuclear collisions, additional acoplanarity may be induced by jet interactions in hot QCD matter [25,[27][28][29]67], with magnitude related to the jet transport parameterq [27,29,67]. Acoplanarity from vacuum radiation grows with both jet energy and √ s, so that low energy jets may have greatest sensitivity toq [27,29].…”
Section: Medium-induced Acoplanaritymentioning
confidence: 99%
“…Suppression of jet yield in central compared to the yield in peripheral collisions with the same jet cone radius R measures the energy transported to angles larger than R. Comparison of recoil jet yield at different R measures medium-induced modification of jet shape (intra-jet broadening [25][26][27]). The distribution of ∆φ measures medium-induced acoplanarity (inter-jet broadening).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 DiFEC can be made by reacting fluorine gas with ethylene carbonate or by a replacement reaction with dichloroethylene carbonate. 21 Mitsui et al 20 found that adding 5 wt% DiFEC and 0.5% lithium difluorophosphate to EC:EMC 1:1 electrolyte improved the high temperature cycling performance of LiCoO 2 /graphite cells, cycled between 3.0 and 4.2 V. Linear fluorinated carbonates, such as bis(2,2,2-trifluoroethyl) carbonate (TFEC) and methyl-2,2,2-trifluoroethyl carbonate, have been investigated as flame retardant additives or co-solvents in Li-ion cells. 8,[22][23][24][25] The re-sults of these studies suggested that fluorinated organic carbonates increased electrolyte stability toward charged electrodes at high voltages.…”
mentioning
confidence: 99%
“…8. Considering volatility loss of Na in the sintering process, the Na 3 As precursor powder, Fe and As powder were mixed according to mole ratio of Na:Fe:As at sodium site that contribute to generate carriers [9,11].…”
Section: Methodsmentioning
confidence: 99%